2016
DOI: 10.1007/s10815-016-0792-3
|View full text |Cite
|
Sign up to set email alerts
|

Single center validation of routine blastocyst biopsy implementation

Abstract: PurposeThe study aims to contrast the efficacy of trophectoderm biopsy preimplantation genetic screening (PGS)/vitrification (VTF)-all cycles to past treatment protocols. Specifically, do these applied technologies increase live birth rates on a per cycle/first transfer basis?Materials and methodsAn observational, retrospective cohort study of first transfer outcomes was performed in two groups. Group 1 (PGS) included PGS/VTF-all cycles, and group 2 (no PGS) included the first transfer from non-PGS fresh cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 13 publications
5
36
0
Order By: Relevance
“…Using this higher concentrated glycerol-based solution, devoid of DMSO, in a highly effective noncommercial aseptic, closed system, 51 has revealed that high pregnancy outcomes can routinely occur across all age groups without the pre-vitrification application of blastocoel collapsing. 40,62 It has become increasingly evident, since first proposed by Grifo et al, 80 that the transfer of a single euploid vitrified/ warmed blastocyst, independent of age, is the most efficient way to achieve a high implantation rate and live birth rate (IR/LBR), as clearly confirmed in other recent reports. 35,62 Furthermore, although there is no difference in IR/LBR using either day 5 or day 6 euploid blastocysts, the miscarriage rate tends to be higher using a day 6 early to full blastocysts (grade ≤3) or embryos with B-quality trophectoderm.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Using this higher concentrated glycerol-based solution, devoid of DMSO, in a highly effective noncommercial aseptic, closed system, 51 has revealed that high pregnancy outcomes can routinely occur across all age groups without the pre-vitrification application of blastocoel collapsing. 40,62 It has become increasingly evident, since first proposed by Grifo et al, 80 that the transfer of a single euploid vitrified/ warmed blastocyst, independent of age, is the most efficient way to achieve a high implantation rate and live birth rate (IR/LBR), as clearly confirmed in other recent reports. 35,62 Furthermore, although there is no difference in IR/LBR using either day 5 or day 6 euploid blastocysts, the miscarriage rate tends to be higher using a day 6 early to full blastocysts (grade ≤3) or embryos with B-quality trophectoderm.…”
mentioning
confidence: 66%
“…40,62 It has become increasingly evident, since first proposed by Grifo et al, 80 that the transfer of a single euploid vitrified/ warmed blastocyst, independent of age, is the most efficient way to achieve a high implantation rate and live birth rate (IR/LBR), as clearly confirmed in other recent reports. 35,62 Furthermore, although there is no difference in IR/LBR using either day 5 or day 6 euploid blastocysts, the miscarriage rate tends to be higher using a day 6 early to full blastocysts (grade ≤3) or embryos with B-quality trophectoderm. 81 Whether PGS is applied, or not, it is routinely accepted that blastocyst viability is not compromised by vitrification, nor micromanipulation, and that delayed ET cycles using the warmed blastocyst can be advantageous.…”
mentioning
confidence: 66%
See 3 more Smart Citations